Memory, gender and sexuality: a post-structuralist approach (Research, Society and Development, 2022)
This paper aims to discuss, in a panoramic way, issues of gender and sexuality evoked in collective memory, in order to bring its importance within a post-structuralist approach, without closing of senses. For such, it was made use of the concept of memory, especially the collective memory and social frames of memory in Maurice Halbwachs (1990; 2004), which brings the notion of shared memory among social groups and replicated as valid truths within that time and space, anchored in frames and milestones. It was verified, through a bibliographic research, that memory is always constituted in a group, and the individual who remembers, in turn, is inserted in this. Thus, this group, which shares the collective memories shared there, uses, most of the time, these memories as rules of faith and practice when there is the reinforcement and influence of larger institutions, which make use of the maintenance of a standardized moral logic of living well. It was also observed that fitting into characteristics considered standard in society is a construction of social groups, and are often used as a form of violence against minority groups such as women, transvestites, transgenders, and subjects with homo-affective sexualities. In this sense, it is up to the academy to promote debates and epistemological constructions that move towards breaking these structural constructs of gender, sexualities, and social roles within a perspective and collective memory standardized by the look of conservative groups that are averse to diversity.